Life events, depression and anxiety in a university population - Aytar, Güler. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1985., 1985)
This study investigated mainly relationships among perception of life events, depression and anxiety in a university population. Additionally, prevalence of depression and level of trait anxiety of the medical faculty students have been investigated. The theoretical framework of the study was based on cognitive theory of depression (Beck, 1967). The general hypothesis of the investigation was that there is positive relationship between negative perception of life events, depression and anxiety. The participants of the study were 306 medical faculty students at Istanbul Faculty of Medicine. The instruments were the Life Experiences Survey, the Beck Depression Inventory and the STAI A-Trait scale. Pearson Product-Moment Correlation Coefficient was used to analyze the data. The results confirmed the general and operational hypotheses.
Keywords: College students -- Conduct of life.; College students -- Psychology.; Anxiety in adolescence.; Depression in adolescence.